Repeated Occurrences of Basal Cell Cancer in Patients With Inflammatory Bowel Disease Treated With Immunosuppressive Medications. (August 2020) - Khan, Nabeel; Patel, Dhruvan; Trivedi, Chinmay; Kavani, Himanshu; Medvedeva, Elina; Pernes, Tyler; Xie, Dawei; Lewis, James; Yang, Yu-Xiao
Abstract : INTRODUCTION: There are limited data on repeated basal cell cancer (BCC) occurrences among patients with inflammatory bowel disease (IBD), especially the impact of continuing immunosuppressive medications. METHODS: We conducted a retrospective cohort study of 54, 919 patients with IBD followed in the Veterans Affairs Healthcare System. We identified patients who had an incident BCC after their IBD diagnosis. We defined patients' exposure based on their IBD medications use as follows: (i) only aminosalicylate (5-ASA) use, (ii) only active thiopurine (TP) use, (iii) past TP use (discontinued >6 months ago) and no antitumor necrosis factor (TNF) use, (iv) anti-TNF use after previous TP use, (v) only anti-TNF use, and (vi) active anti-TNF and TP use. The outcome of interest was the repeated occurrence of BCC. Adjusted and unadjusted hazard ratios with 95% confidence intervals were used to estimate the risk of repeated BCC occurrence. RESULTS: A total of 518 patients developed BCC after their IBD diagnosis. The numbers of repeated BCC occurrences per 100 person-years were 12.8 (5-ASA use only), 34.5 (active TP use), 19.3 (past TP use and no anti-TNF use), 25.4 (anti-TNF use after previous TP use), 17.8 (only anti-TNF use), and 22.4 (active anti-TNF and TP use). Compared with 5-ASA use alone, only active TP use was associated with an increased risk for repeated BCC occurrence (adjusted hazard ratio 1.65, 95% confidence interval 1.24–2.19; P = 0.0005). However, the increased risk was no longer present for other exposure categories. DISCUSSION: Among IBD patients who developed an incident BCC while taking a TP and continued it, there was an increased risk of repeated BCC occurrences.